2019
DOI: 10.3389/fpsyg.2019.02221
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Emoji: Current Research and Future Perspectives

Abstract: A growing body of research explores emoji, which are visual symbols in computer mediated communication (CMC). In the 20 years since the first set of emoji was released, research on it has been on the increase, albeit in a variety of directions. We reviewed the extant body of research on emoji and noted the development, usage, function, and application of emoji. In this review article, we provide a systematic review of the extant body of work on emoji, reviewing how they have developed, how they are used differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
205
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(224 citation statements)
references
References 147 publications
(216 reference statements)
2
205
0
17
Order By: Relevance
“…These symbols indicate Bridgit's positive emotions—that she enjoyed the text chat—as well as her feelings of closeness to S. Her partner S also used various pictorial signs at the end of his response, expressing feelings of fun and friendliness (2). Use of emojis facilitates communication and enhances interactions, and frequent use of emojis shows a user's emotional stability, extroversion and agreeableness (Bai, Dan, Mu, & Yang, 2019). Symbols of this type are useful to express emotions and add intimacy to written texts, which lack nonverbal cues such as facial expressions and gestures.…”
Section: Resultsmentioning
confidence: 99%
“…These symbols indicate Bridgit's positive emotions—that she enjoyed the text chat—as well as her feelings of closeness to S. Her partner S also used various pictorial signs at the end of his response, expressing feelings of fun and friendliness (2). Use of emojis facilitates communication and enhances interactions, and frequent use of emojis shows a user's emotional stability, extroversion and agreeableness (Bai, Dan, Mu, & Yang, 2019). Symbols of this type are useful to express emotions and add intimacy to written texts, which lack nonverbal cues such as facial expressions and gestures.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the WhatsApp group dynamic presented the features of emotional contagion as well, where emotions were shared among the interacting netizens in the digital environment, influencing the spread of information and attitudes [ 18 , 19 ]. The emotions were specifically shared through emojis, which were abundantly used in composing the message (37% of the messages), showing predominantly positive emotions [ 20 ]. Interestingly, the dynamics of this study’s WhatsApp group can be compared to the recently published emotional contagion simulation on rumor refuting, which indicates that after initial input, the group will stabilize in 4 days (same as in the group in this study), and that none of the subjects would act negatively to what has happened but rather positively (agreeing with the initial input) or neutrally (indifferent to the topic) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foods 2020, 9, x [14] that are language-independen expressions of emotional experienc Previous studies have selecte focus groups [10] or check-all-that Although emoji were found to be a is known about how children inter food.…”
Section: ) Crying Facementioning
confidence: 99%
“…These studies recognized the advantage of using emoji to measure food-elicited emotions, which are intuitive, easy-to-use and child-friendly. Emoji are supposed to simulate facial expressions that convey specific emotions or other situational meanings [ 14 ] that are language-independent indicators of emotions [ 15 ] and can help to elicit spontaneous expressions of emotional experiences elicited by foods [ 16 ].…”
Section: Introductionmentioning
confidence: 99%